Microbial community structure and biodiversity of size-fractionated granules in a partial nitritation–anammox process - Luo, Jinghuan; Chen, Hui; Han, Xiaoyu; Sun, Yanfang; Yuan, Zhiguo; Guo, Jianhua (FEMS microbiology ecology, 2017)
Abstract The performance of a granule-based partial nitritation–anammox process is expected to be affected by the granule size distribution, but little is known about the impact of granule size on microbial community structure and diversity. To reveal how the microbial composition and diversity vary with granule size, granules from a partial nitritation–anammox reactor were size-fractionated into five classes (<0.2, 0.2–0.5, 0.5–0.8, 0.8–1.0 and >1.0 mm). Microbial communities and diversity in these size-fractionated granules were investigated using 16S rRNA gene high-throughput sequencing. It was found that larger granules harbor more diverse microbial communities than small granules. Both quantitative PCR and 16S rRNA gene sequencing indicated that the abundance of anammox bacteria (dominated by Candidatus Brocadia) exhibited an increasing trend with granule size. In contrast, the abundance of ammonia-oxidizing bacteria (Nitrosomonas) decreased with increasing granule size. Moreover, larger granules harbored more diverse anammox bacteria, with four genera found in the largest granules while only two with limited abundance were detected in the smallest granules. The findings highlight an important role for granule size in shaping community structure and biodiversity. Larger granules harbor more diverse microbial communities.